2013
DOI: 10.1186/1745-6673-8-5
|View full text |Cite
|
Sign up to set email alerts
|

A prospective investigation of injury incidence and risk factors among army recruits in combat engineer training

Abstract: BackgroundUnited States Army combat engineer (ENG) training is an intense 14-week course designed to introduce new recruits to basic soldiering activities, Army values and lifestyle, and engineering skills and knowledge. The present investigation examined injury rates and injury risk factors in ENG training.MethodsAt the start of their training, 1,633 male ENG recruits were administered a questionnaire containing items on date of birth, height, weight, tobacco use, prior physical activity, and injury history. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
30
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 72 publications
5
30
0
4
Order By: Relevance
“…Specifically, Knapik et al [35] reported 50.7% incidence in US Infantry and 47% over fourteen weeks US combat Engineer training, but comparable with those reported by Lisman et al [36] who observed among male recruits undergoing a twelve week US Marine Corps Boot Camp (39.6%), and Kaufman et al [6] who reported 33.1% in male Naval Specialist Warfare training. All of which fall beneath the 75% incidence rate for musculoskeletal lesions found among the French military [12].…”
Section: Injury Incidencesupporting
confidence: 53%
“…Specifically, Knapik et al [35] reported 50.7% incidence in US Infantry and 47% over fourteen weeks US combat Engineer training, but comparable with those reported by Lisman et al [36] who observed among male recruits undergoing a twelve week US Marine Corps Boot Camp (39.6%), and Kaufman et al [6] who reported 33.1% in male Naval Specialist Warfare training. All of which fall beneath the 75% incidence rate for musculoskeletal lesions found among the French military [12].…”
Section: Injury Incidencesupporting
confidence: 53%
“…It can be also due to sudden increase in amount and intensity of physical activity along with repeated impact due to running on hard surface, improper technique and equipment [2,8].…”
Section: Methodsmentioning
confidence: 99%
“…As demais 24 perguntas são relativas a quatro domínios e suas respectivas facetas: Domínio I: Físico, focalizando as facetas: Dor e desconforto; Energia e fadiga; Sono e repouso; Atividades da vida cotidiana; Dependência de medicação ou de tratamentos; Capacidade de trabalho. Embora alguns profissionais que lidam com tarefas perigosas, como os policiais, afirmem que um pouco de estresse no trabalho é positivo (7) , a exposição a jornadas de trabalho extensivas e intensas e a situações estressantes, vivenciadas pelos policiais, favorecem o desenvolvimento de problemas de saúde que podem se cronificar ao longo do tempo, se não receberem atenção especial (8) . Nesse sentido, destaca-se que o sofrimento humano é intrínseco aos processos de trabalho.…”
Section: Casuística E Métodosunclassified